2010
DOI: 10.1186/1472-6963-10-311
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable readmission in Hong Kong - system, clinician, patient or social factor?

Abstract: BackgroundStudies that identify reasons for readmissions are gaining importance in the light of the changing demographics worldwide which has led to greater demand for hospital beds. It is essential to profile the prevalence of avoidable readmissions and understand its drivers so as to develop possible interventions for reducing readmissions that are preventable. The aim of this study is to identify the magnitude of avoidable readmissions, its contributing factors and costs in Hong Kong.MethodsThis was a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 12 publications
5
84
0
1
Order By: Relevance
“…Minimal interactions among specialists and limited information to the general practitioner and patient lead to a fragmented health approach, non-concerted and sometimes ineffective interventions, a scattered follow-up and a suboptimal cost-effectiveness ratio. 26,27 The amalgamation of P4 medicine with other prevailing concepts and principles has the potential to reinvent healthcare. 28 In the current concept paper, we propose the P4 Health (P4H) continuum model, which embraces and expands upon the concepts of P4 medicine 24 , as a framework to promote and facilitate pro-active collaborations with a common orchestrated language and integrated care model.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Minimal interactions among specialists and limited information to the general practitioner and patient lead to a fragmented health approach, non-concerted and sometimes ineffective interventions, a scattered follow-up and a suboptimal cost-effectiveness ratio. 26,27 The amalgamation of P4 medicine with other prevailing concepts and principles has the potential to reinvent healthcare. 28 In the current concept paper, we propose the P4 Health (P4H) continuum model, which embraces and expands upon the concepts of P4 medicine 24 , as a framework to promote and facilitate pro-active collaborations with a common orchestrated language and integrated care model.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] There are relatively few studies examining the risk factors for readmission among all primary care patients, and many of these were performed outside the United States or in hospitalist practices. 10,[22][23][24][25] It is well known that a small proportion of patients account for a disproportionate number of hospital admissions and health care costs. 26 -28 Identifying these patients is important for quality of care and economic reasons.…”
mentioning
confidence: 99%
“…14,16,17 For example, patient population has an impact on readmission rates with minority populations and those of lower socioeconomic status being at much higher risk for readmission. 14,18,19 If a standard readmission rate is adopted without some adjustment for the type of population a hospital receives, those institutions serving the patients most in need will be unfairly penalized. Although gynecologic oncology is not the main target of current guidelines, it is near certain that further regulations will have an impact in the future.…”
Section: Discussionmentioning
confidence: 99%
“…3 Given the current trend, it is reasonable to expect that the number of applicable conditions will expand in the future. 4 In their highly influential study, Jencks et al 5 analyzed over 11 million Medicare patient medical admissions and found a 30-day readmission rate of 19.6% of which only 10% were estimated to be planned. The cost of these unplanned rehospitalizations was calculated to be $17.…”
mentioning
confidence: 99%